PROMOTION OF PARENT’S COMPETENCE IN INFANT FLOATING - Kurmeļeva, Alīna; Fernāte, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Currently, there are conflicting views around the world regarding infant floating. There is no consensus on the most effective techniques for facilitating infant swimming skills. Infant floating is dominated by a therapeutic and pedagogical approach that ensures parents' involvement in the process. There is no unified methodology for infant floating in Latvia. Furthermore, the number of infant swimming specialists, as well as adequate infrastructure, is insufficient and limited. In the existing situation, it is important to increase parents' competence in infant floating so that parents are able to carry out infant bathing independently. The aim of the study is to develop a model for improving parental competence in infant floating. The main research methods comprised of studying and analysing scientific literature and modelling. The paper is based on 27 scientific literature sources, 22 of them in English, 2 in Latvian and 3 in Russian. The developed model of parental competence improvement in infant floating includes parents' theoretical knowledge of infant floating; independent research on infant floating; water safety; the application of infant floating skills under a specialist’s guidance and the ability to independently use acquired skills without guidance. In the future it will be possible to test the developed model to evaluate its usefulness in promoting parental competence in infant floating, thus ensuring parents' ability to float the infant independently.